Running Event “Trackpresso: 5K Color Run 2024 di Kota Semarang, Jawa Tengah” sebagai Creative & Design Manager - Al Ghifari, Rafdil; Luqman, Yanuar; Naryoso, Agus (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
This project delves into all the preparations and execution of the Trackpresso: 5k Color Run 2024 event. Anak Panah Kopi, as the client, collaborated with the project team based on the desire to create an event that was trending in recent months. As a foundation for this project, this report utilizes the event management framework outlined in Joe Goldblatt's book